The Influence of HR Competence and Organizational Culture on Employee Performance in the Regional Financial and Asset Board of Paser Regency - Mariyani Mariyani; Sofjan Aripin; Darmanto Darmanto (Training & Research Institute - Jeramba Ilmu Sukses, 2023)
Today, employee performance is not only determined by organizational culture, but also competency skills. Speaking of institutional progress, the key internal aspect that must be developed is HR competency. Then, another internal pillar is the strategy to create a harmonious organizational culture climate. This paper serves to determine the causality between HR competence and organizational culture on employee performance. Quantitative models by path analysis are implemented to investigate direct as well as indirect linkages. The study motif focuses on a survey approach that digs up information about variable items to employees at the Regional Financial and Asset Board of Paser Regency. A total of 66 respondents were invited to be interviewed openly. The sample is sampling in nature, where the population size is <100 informants. Supporting equipment uses questionnaires and documentation sessions. Empirical results found that HR competence and organizational culture have a significant effect on employee performance, where the statistical output explains that ρ <0.05. Then, the SPSS output also concludes that HR competencies play a role in a pattern of significant linkages between HR competencies and employee performance (ρ <0.05). Finally, this paper contributes to a theoretical and practical extension to the stakeholders. Expectations on the future agenda need to consider other elements outside the model discussed, which have implications for the performance of government officials.